The Opportunities and Limits of Regional Policy-Making - some Critical Remarks on the Belgian Case - Wouter Blomme; Tine Boucké; Carl Devos; Sofie Staelraeve; Tom Verstraete (European Regional Science Association (ERSA), 2005)
In our paper, we deal with the dynamic and consequences of the federal structure and the dual party system for the policy capacities of Flanders, one of the three regions in the Belgian federal state. Since 1993, the Belgian constitution officially states that Belgium is a federal state. The process of state reform began in 1970, after the birth of linguistic parties in the sixties. One of the main characteristics of the Belgian party system is the absence of Belgian political parties and the asymmetry of the regional party systems. The specific functioning of political parties in 'Belgium', in other words in its regions, has some important consequences for the scope for policymaking of those regions. The differences between the regional party systems are the product of the region-specific social and economical features. In spite of the unequal economic performance of the two main regions, the 'high speed' North and 'slow speed' South, and the different economic challenges and possibilities, the Belgian federal level still retains several of the main economic competences and instruments. Therefore, the regionalised parties must, on the one hand, work together while, on the other hand, need to fight each other because of limited (federal) resources. We will consider the consequences of the elasticity and duality of the party system: does it enable or impede regional policy making, such as the switch of the unequal regional economies to a 'new economy'?
Keywords: 330